Upper Gastrointestinal Bleeding as a Debut Form of Groove Pancreatitis: A Diagnostic Challenge. (7th March 2022) - Matías-García, Belén; Castellón-Pavón, Camilo José; Díaz-García, Gustavo; Manso-Abajo, Belén; Hernández-Aceituno, Daniel; Hermosín-Peña, Antonio; Mejías-Sosa, Luis; Durán-Poveda, Manuel
Abstract : Introduction . Groove pancreatitis (GP) is an unusual subtype of chronic pancreatitis that affects the groove area. Differential diagnosis between groove pancreatitis and pancreatic carcinoma (PC) can be challenging, both clinically and radiologically. Our aim is to report the first case of GP debut with upper gastrointestinal bleeding (UGB). Case Report . A 53-year-old man with a personal history of alcohol and tobacco abuse and chronic pancreatitis was admitted to the hospital for epigastric abdominal pain. A computed tomography scan showed a locally advanced neoformative lesion in the distal stomach. The patient presented melena, arterial hypotension, and 4.4 g/dl of hemoglobin. An upper gastrointestinal endoscopy showed a neoformative ulcerated lesion at the duodenal bulb without active bleeding. Biopsies were taken, and histopathological analysis did not show malignancy. A cephalic pancreaticoduodenectomy was performed, and the postoperative period was uneventful. Histopathological analysis revealed a segmental GP. Discussion . GP is an uncommon entity, and its clinical and radiological presentation mimics PC. However, with advances in imaging tests, several radiological criteria have been described to distinguish GP from PC preoperatively. Although some authors recommend a stepwise management with initial conservative therapy, a therapeutic strategy has not yet been established. Conclusion . GP is an uncommon type of focal pancreatitis that should be considered as a differential diagnosis of PC. We report the first clinical case of GP whose debut with UGB presented a greater diagnostic and therapeutic challenge.